2022
DOI: 10.3389/fcell.2021.781327
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic System Dysfunction in Autism Spectrum Disorders

Abstract: Autism spectrum disorder (ASD) refers to a series of neurodevelopmental diseases characterized by two hallmark symptoms, social communication deficits and repetitive behaviors. Gamma-aminobutyric acid (GABA) is one of the most important inhibitory neurotransmitters in the central nervous system (CNS). GABAergic inhibitory neurotransmission is critical for the regulation of brain rhythm and spontaneous neuronal activities during neurodevelopment. Genetic evidence has identified some variations of genes associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 169 publications
2
37
0
Order By: Relevance
“…As the developmental depolarizing-to-hyperpolarizing switch in GABA transmission is critical for the correct establishment of the E/I balance [ 274 ], alterations in GABAergic signaling can impair normal cellular processing and cause deficits such as those observed in ASD [ 275 ]. To date, increasing evidence of dysfunction in the GABAergic neurotransmission system has been reported in patients and animal models of ASD [ 276 , 277 ]. In vivo 1H-MRS measurements have revealed a significant increase in plasma levels of GABA in children with ASD compared to controls [ 81 , 85 , 278 ].…”
Section: Gaba/glutamate Balance In Asdmentioning
confidence: 99%
“…As the developmental depolarizing-to-hyperpolarizing switch in GABA transmission is critical for the correct establishment of the E/I balance [ 274 ], alterations in GABAergic signaling can impair normal cellular processing and cause deficits such as those observed in ASD [ 275 ]. To date, increasing evidence of dysfunction in the GABAergic neurotransmission system has been reported in patients and animal models of ASD [ 276 , 277 ]. In vivo 1H-MRS measurements have revealed a significant increase in plasma levels of GABA in children with ASD compared to controls [ 81 , 85 , 278 ].…”
Section: Gaba/glutamate Balance In Asdmentioning
confidence: 99%
“…Importantly, it was suggested that the dynamics of the visual rivalry is dependent on brain-wide excitatory-inhibitory balance -a process that is also proposed to be altered in autism, leading to the expression of core traits of ASD (reviewed in Zhao et al, 2022). Finally, our visual rivalry paradigm utilizes a bistable moving plaid, in which the subject's perception switches between the local motionbased, 'transparent' interpretation of the stimulus versus the global motion-based, 'coherent' interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate and GABA, functioning respectively as the primary excitatory [ 124 ] and inhibitory [ 125 ] neurometabolites in the central nervous system, play various key physiological roles (e.g., inflammation [ 126 ]), including the processing and modulation of pain [ 87 ]. Alterations in the metabolism of both molecules have been associated with chronic pain [ 88 ].…”
Section: Gut Microbiome Metabolites As Possible Contributors To Painmentioning
confidence: 99%